CSPCR: Cloud Security, Privacy and Compliance Readiness - A Trustworthy Framework - Sugandh Bhatia; Jyoteesh Malhotra (Institute of Advanced Engineering and Science, 2018)
The privacy, handling, management and security of information in a cloud environment are complex and tedious tasks to achieve. With minimum investment and reduced cost of operations an organization can avail and apply the benefits of cloud computing into its business. This computing paradigm is based upon a pay as per your usage model. Moreover, security, privacy, compliance, risk management and service level agreement are critical issues in cloud computing environment. In fact, there is dire need of a model which can tackle and handle all the security and privacy issues. Therefore, we suggest a CSPCR model for evaluating the preparation of an organization to handle or to counter the threats, hazards in cloud computing environment. CSPCR discusses rules and regulations which are considered as pre-requisites in migrating or shifting to cloud computing services.